Following the faith of the father; Sayyid 'Uthm n's son Ya y on mosque etiquette - Wieringa, E. P. (Wacana, Journal of the Humanities of Indonesia, 2014)
The Dal 'il al-n shid 'an a k m al-wal 'im f -l-mas jid (Arguments of the Seeker for Legal Judgements concerning Festive Meals in Mosques) is a short tract, written in 1938 in Malay in Arabic script by Ya y b. 'Uthm n b. 'AbdAll h, none other than a son of the renowned Batavian muft Sayyid 'Uthm n (1822-1914). Protesting against the (in his view) bid'a (unauthorized religious innovation) () of organizing festive meals in mosques, he felt it his duty to try to stop his co-religionists from doing wrong. Not being a theologian himself, his pamphlet is basically a tissue of quotations drawn from the prolific work of his well-known father.